Serum Angiopoietin-like Protein 6, Risk of Type 2 Diabetes, and Response to Hyperglycemia: A Prospective Cohort Study - Fan, Kang-Chih; Wu, Hung-Tsung; Wei, Jung-Nan; Chuang, Lee-Ming; Hsu, Chih-Yao; Yen, I-Weng; Lin, Chia-Hung; Lin, Mao-Shin; Shih, Shyang-Rong; Wang, Shu-Huei; Chang, Tien-Jyun; Li, Hung-Yuan (The journal of clinical endocrinology and metabolism, 2020)
Abstract Context Angiopoietin-like protein 6 (ANGPTL6) is a hepatokine that improves insulin sensitivity in animals. However, serum ANGPTL6 concentration was found to be higher in human participants with diabetes or metabolic syndrome in cross-sectional studies, implying that ANGPTL6 may be induced to counteract hyperglycemia. Objective To investigate whether serum ANGPTL6 can predict incident diabetes and explore whether glucose or insulin can regulate ANGPTL6 expression and secretion. Design This cohort study included adults without diabetes at baseline who were followed every 2 years for incident diabetes. Serum ANGPTL6 concentrations were measured at baseline and during oral glucose tolerance tests (OGTTs). A hepatic cell line, HepG2, and diet-induced obesity mouse model were used to evaluate the response of ANGPTL6 expression and secretion to hyperglycemia and the metabolic syndrome. Results We recruited 1103 participants without diabetes at baseline. During the 4.22-year follow-up, 113 (10.2%) participants developed incident diabetes. Serum ANGPTL6 was negatively associated with the incidence of diabetes (adjusted hazard ratio, 0.77; P = 0.042). However, serum ANGPTL6 level was higher in participants with prediabetes (P = 0.018) and was elevated during OGTT. In HepG2 cells, treatment with glucose, but not insulin, induced ANGPTL6 expression. Hepatic ANGPTL6 expression and serum ANGPTL6 concentrations were significantly higher in mice fed with a high-fat diet than in those fed with a standard chow (both P < 0.05). Conclusion A high serum ANGPTL6 level is associated with a low incidence of diabetes in humans. ANGPTL6 is expressed and secreted in response to hyperglycemia to maintain glucose homeostasis.